Time-dependent seismic fragility analysis of bridge systems under scour hazard and earthquake loads. (15th August 2016) - Guo, Xuan; Wu, Yingkui; Guo, Ya
Highlights: Scour and earthquake effects on the failure of bridges are studied. Time-dependent fragility analysis is adopted to study the performance of bridges. Uncertainties of materials, scour depth, and ground motions are considered. Abstract: A scoured-bridge system has the potential to be subject to earthquake loads. In a bridge's service life, the depth of the scour hole may gradually increase with time due to future flood events. So, scour is a time-dependent hazard. Few efforts have been made to investigate the time-dependent scour hazard on bridge systems under seismic loads. In this work, time-dependent seismic fragility analysis is adopted to study scoured-bridge systems under earthquake loads across a bridge's whole service life. Through time-dependent fragility analysis, the annual fragility curves for different damage states of the bridge systems under combined hazards can be obtained efficiently, in which the uncertainty of materials, scour depth, and ground motions are considered with the Latin Hypercube Sampling method. Also, the fragility surfaces for different damage states can be obtained, which is conditional on both bridge service time and seismic intensity. By combining the fragility surface with earthquake hazards at a given site, the annual seismic risk or cost of scoured-bridge systems can be calculated. Two bridge models are used for the time-dependent fragility analysis. The results show that the probability of all the damage states increases with both time and seismic intensity; however, it does not increase linearly with time and seismic intensity. The nonlinearity depends on the severity of damage state. The damage probability is affected much less by time and seismic intensity if they are below certain thresholds. Then it quickly increases with both time and seismic intensity before another threshold is reached. The thresholds for both stages of time and seismic intensity become bigger when the severity of the damage state changes from slight damage to collapse.